Estimating today's cosmological constant via the Zel'dovich-holographic connection. (1st January 2023) - Tello, Pablo G.; Bini, Donato; Kauffman, Stuart; Succi, Sauro
Abstract: This letter proposes an approach to the vacuum energy and the cosmological constant (CC) paradox based on the Zel'dovich's ansatz, which states that the observable contribution to the vacuum energy density is given by the gravitational energy of virtual particle-antiparticle pairs, continually generated and annihilated in the vacuum state. The novelty of this work is the use of an ultraviolet cut-off length based on the holographic principle, which is shown to yield current values of the CC in semi-quantitative agreement with experimental observations.